La communauté Nova Esperança (PR) : l'incorporation des droits des migrants internationaux et des réfugiés aux revendications des mouvements de lutte pour le logement au Brésil - Elaine Cristina Schimtt Ragnini; Daniele Regina Pontes; José Ricardo Vargas de Faria; Márcio de Oliveira (Confins)
The Comunidade Nova Esperança was created in 2020 in a public space on the outskirts of the city of Curitiba, capital of the state of Paraná, based on the actions of the Popular Movement for Housing (PMH). The occupied area, with a total area of ​​371,420.23 m2, belongs to the Social Action Foundation, a public entity linked to the Municipality of Curitiba. As it is an occupation, the area is currently subject to a lawsuit for repossession. Faced with the need to clarify the characteristics of the area, the Parquet of the State of Paraná requested the Federal University of Paraná (UFPR) to carry out a technical study on the possibilities of use, occupation and subdivision of the area and the environmental conditions since it is located in a municipality with fragile environment. In this study, we analyze the environment, general living conditions, housing and ways of generating income of about 1,200 families, of which 65% are between 25 and 59 years old and ¼ of them are immigrants particularly affected by the pandemic and the economic crisis. Overall, we identified the state's omission in housing and social protection policies. In the opposite direction, in the community, residents preserve the forest, organize solid waste collection, build biodigesters and certain septic tank structures to reduce soil and groundwater contamination. In addition, there is a community garden, a collective kitchen and a sewing workshop. The occupied area is an obvious solution to the housing deficit. Furthermore, income generation and new forms of sociability between Brazilians and immigrants are examples that can inspire the implementation of reception and integration policies.